Level of empathic orientation in students of physical therapy and rehabilitation of a state university - Cañamero Riquelme, Jorge Luis (2017)
Objective: To determine the level of empathic orientation in students of Physical Therapy and Rehabilitation of Universidad Nacional Mayor de San Marcos (UNMSM), 2016. Materials and methods: A quantitative descriptive-observational prospective non-experimental cross-sectional study performed in 134 second- to fifth-year students of Physical Therapy and Rehabilitation at Escuela Académico Profesional de Tecnología Médica of UNMSM. The Jefferson Scale of Empathy (JSE) was used. Results: In general, a mean score of 114.60 ± 14.424 was obtained, corresponding to a high level of empathic orientation. This category is qualitatively represented by 85.1%. Regarding the dimensions, mean scores were obtained in “Perspective Taking” (61.33, high level [91.0%]), “Compassionate Care” (41.16, high level [82.8%]) and “Standing in the Patient’s Shoes” (12.38, mean level [61.2%]). There were no significant differences neither in general terms nor in gender and age (p>0.05), but there were significant differences in the year of the career. Conclusion: Third, fourth and fifth-year students of Physical Therapy and Rehabilitation of Universidad Nacional Mayor de San Marcos have a favorable empathic orientation compared to second-year students (p≤0.05). They specifically show willingness to understand patients’ feelings and pay attention to patients’ personal experiences as therapeutic means.